Outdoor system for smart office - Tan Kian Haw (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
Currently, the automation technologies are available commercially. Basically, this system is designed to be implemented in the outdoor system for smart office. This project is applicable to all sorts of building such as campus, hospital, shopping mall, big company and etc. As a result it saves money, is a more pleasant place in which to work and goes easier on the environment. This project consists of the construction of hardware and software system by using microcontroller 8051. The system will automatically turn on the corridor lights during night time and turned off during day time. It also comprises manual switching in case user needs to have light during the day. After that, the Liquid Crystal Display (LCD) will display the greeting phrases, current time and current date. Besides that this system is capable to open the front gate lock automatically when the infrared sensor is detected. The security buzzer and lights are activated when the back door is open by someone. The shade is open automatically during the raining day when the water/rain sensor is detected. Temperature sensor LM35 is used to develop the automatic fan system. The system design is successfully developed at a very low cost.